2013
DOI: 10.1063/1.4804963
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the structural, magnetic, and magnetostrictive properties of zinc-substituted cobalt ferrite

Abstract: This study presents the effects of substitution of Zn 2+ for Co2+ at low concentrations and the effects of temperature variations on the structural, magnetic, and magnetostrictive properties ofcobalt ferrite. Although the Zn-substituted cobalt ferrite samples, Co1−x Zn xFe2O4 (x = 0.02, 0.04, 0.06, 0.09, and 0.17) did not show observable changes in crystal structure, the magnetic and magnetostrictive properties were strongly affected. The variation in magnetic susceptibilitywith composition can be related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 24 publications
2
33
1
Order By: Relevance
“…) This trend in materials based on cobalt ferrite has been explained on the basis of the competition between the thermal energy and the magnetocrystalline anisotropy energy in response to the applied magnetic field. 14 As temperature decreased from 400 K, the applied magnetic field increasingly became more effective in aligning the magnetic moments in its direction. This results in increased saturation magnetization as seen in regime 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…) This trend in materials based on cobalt ferrite has been explained on the basis of the competition between the thermal energy and the magnetocrystalline anisotropy energy in response to the applied magnetic field. 14 As temperature decreased from 400 K, the applied magnetic field increasingly became more effective in aligning the magnetic moments in its direction. This results in increased saturation magnetization as seen in regime 1.…”
Section: Resultsmentioning
confidence: 99%
“…2 which compares the saturation magnetization of the heat treated samples to those of Zn-substituted cobalt ferrite. 14 The mechanism by which heat treatment results in the increase in saturation magnetization is cation redistribution arising due to increased ionic mobility at elevated temperatures. It has been shown that annealing and quenching of cobalt ferrite results in the increased occupancy of Fe 3þ on the octahedral sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…information storage systems, 1 ferro-fluid technology, 2 magnetic refrigeration, 3 magnetic diagnostics, 4 and magnetostriction. 5 In cobalt-ferrite the presence of doping elements and the thermal history during the synthesis and processing alter the metal ions distribution and hence influence their structural and magnetic properties. 6 The lanthanide series elements/ions have a net magnetic moment that depends upon the number of f-orbital electrons; and among them Er þ3 is relatively small in size (89 pm), and has relatively high magnetic moment (7 l B ).…”
mentioning
confidence: 99%